Targeted Y chromosome capture enrichment in admixed South American samples with haplogroup Q - Köksal, Zehra (2022)
Y haplogroups, defined by Y-SNPs, allow the reconstruction of the human Y chromosome genealogy. Recently, MPS based panels were introduced in the forensic genetics community for Y-SNP typing and identification of a broad range of haplogroups. The panels are based on an amplicon strategy and allow the detection of up to 15,600 Y-SNPs. The panels target up to 210,000 bps, which should be compared to the overall 8.9 Mbps comprising the unique regions of the non-recombining portion of the Y chromosome (NRY). We present an alternative approach of sequencing unique regions within the NRY using target enrichment probes and hybridization capture. A total of 359,954 probes were designed using the SureDesign software, representing 7.5 Mbps of the NRY. Library preparation and capture were performed using the Agilent SureSelect XT HS2 Target Enrichment method and sequencing was performed in a NovaSeq 6000 System. Besides individual barcodes, the method also included unique molecular barcodes for additional quality screening. The method was tested on admixed South Americans that carry a Y chromosome of haplogroup Q. We successfully identified novel variation that could potentially help refining haplogroup Q phylogeny.